Rhodium-Catalyzed Annulation of 2-Arylimidazoles and α-Aroyl Sulfoxonium Ylides toward 5-Arylimidazo[2,1-a]isoquinolines - Yang, Rui; Wu, Xiaopeng; Sun, Song; Yu, Jin-Tao; Cheng, Jiang (Synthesis, 2018)
A Rh-catalyzed annulation between 2-aryl-1H-benzo[d]imidazoles and α-aroyl sulfoxonium ylides was developed, affording a series of benzimidazo[2,1-a]isoquinolines in moderate to excellent yields. This procedure proceeded with the sequential ortho-C–H functionalization and cyclization, representing a facile and straightforward pathway to access such frameworks.
Keywords: rhodium catalysis; annulation; sulfoxonium ylides; 2-arylimidazoles; isoquinolines